'Charlie Is So Cool Like': Authenticity, Popularity and Inclusive Masculinity on YouTube. (December 2015) - Morris, Max; Anderson, Eric
On the world's most utilised video-sharing social networking site, YouTube, Charlie McDonnell ( Charlieissocoollike ), Dan Howell ( Danisnotonfire ) and Jack and Finn Harries ( JacksGap ) are Britain's most popular video-bloggers (vloggers). With more than two million regular subscribers to each of their channels, along with millions of casual viewers, they represent a new form of authentic online celebrity. These young men, whose YouTube careers began as teenagers, do not espouse a traditional form of masculinity; they are not sporty, macho or even expressly concerned with being perceived as heterosexual. Instead, they present a softer masculinity, eschewing the homophobia, misogyny and aggression attributed to boys of previous generations. These behaviours are theorised using Anderson's Inclusive Masculinity Theory. Drawing on analysis of 115 video-blogs (vlogs), along with an in-depth interview with Charlie McDonnell, this article examines how these young men developed and exhibit their inclusive masculinities and attitudes, which we postulate are a reflection of dominant youth culture.